Monoaminergic tone supports conductance correlations and stabilizes activity features in pattern generating neurons of the lobster, Panulirus interruptus - Krenz, Wulf-Dieter; Parker, Anna R.; Rodgers, Edmund; Baro, Deborah J. (Frontiers in Neural Circuits, 2015)
Experimental and computational studies demonstrate that different sets of intrinsic and synaptic conductances can give rise to equivalent activity patterns. This is because the balance of conductances, not their absolute values, defines a given activity feature. Activity-dependent feedback mechanisms maintain neuronal conductance correlations and their corresponding activity features. This study demonstrates that tonic nM concentrations of monoamines enable slow, activity-dependent processes that can maintain a correlation between the transient potassium current (IA) and the hyperpolarization activated current (Ih) over the long-term (i.e., regulatory change persists for hours after removal of modulator). Tonic 5nM DA acted through an RNA interference silencing complex (RISC)- and RNA polymerase II-dependent mechanism to maintain a long-term positive correlation between IA and Ih in the lateral pyloric neuron (LP) but not in the pyloric dilator neuron (PD). In contrast, tonic 5nM 5HT maintained a RISC-dependent positive correlation between IA and Ih in PD but not LP over the long-term. Tonic 5nM OCT maintained a long-term negative correlation between IA and Ih in PD but not LP; however, it was only revealed when RISC was inhibited. This study also demonstrated that monoaminergic tone can also preserve activity features over the long-term: The timing of LP activity, LP duty cycle and LP spike number per burst were maintained by tonic 5nM DA. The data suggest that low-level monoaminergic tone acts through multiple slow processes to permit cell-specific, activity-dependent regulation of ionic conductances to maintain conductance correlations and their corresponding activity features over the long-term.